2019
DOI: 10.5267/j.msl.2019.3.003
|View full text |Cite
|
Sign up to set email alerts
|

Financial depth and economic growth: Empirical evidence from ASEAN+3 countries

Abstract: Nexus between financial depth and economic growth has been studied for long time and still attracts great attention from policymakers. This research examines the relationship among ASEAN+3 countries from 2000 to 2014 based on Cobb-Douglas theoretical framework. The results show that financial depths measured by domestic credit to private sector, M3 and stock market capitalisation all have significant effects on economic growth. The paper also gives policy recommendations to promote financial development for pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 28 publications
3
5
0
2
Order By: Relevance
“…The contributions made by capital and money markets have proven their important nexus with economic growth and are well recognized as significant intermediate conduits driving economic growth by scholars ( Bukowski and Zięba, 2019 ; Destek et al., 2020 ; Haseeb et al., 2019 ; Hassan et al., 2020 ; Karimo and Ogbonna, 2017 ; Le, 2020 ; Le et al., 2019 ; Lestari et al., 2020 ; Ncanywa and Mabusela, 2019 ; Twinoburyo and Odhiambo, 2018 ), academics, and policymakers. But it is important to understand the magnitude of the effects of capital and money market indicators on economic growth, which is truly essential to help policymakers construct specific policies in light of the macroeconomic variables ( Chen et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The contributions made by capital and money markets have proven their important nexus with economic growth and are well recognized as significant intermediate conduits driving economic growth by scholars ( Bukowski and Zięba, 2019 ; Destek et al., 2020 ; Haseeb et al., 2019 ; Hassan et al., 2020 ; Karimo and Ogbonna, 2017 ; Le, 2020 ; Le et al., 2019 ; Lestari et al., 2020 ; Ncanywa and Mabusela, 2019 ; Twinoburyo and Odhiambo, 2018 ), academics, and policymakers. But it is important to understand the magnitude of the effects of capital and money market indicators on economic growth, which is truly essential to help policymakers construct specific policies in light of the macroeconomic variables ( Chen et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Aluko and Ibrahim (2020) also discovered a connection between the influence of financial depth on economic growth and the level of a country's institutional development, with low-institution countries having greater impact from financial deepening than high-institution ones. Le et al (2019), based on a study of ASEAN countries in 2000−2014, concluded that the increase in domestic credit to the private sector has a positive effect with a one-year lag, while improved market capitalization of the stock market has an immediate effect. A study by Jun et al (2007) on the impact of financial deepening on economic growth based on the example of 29 provinces of China in 1987−2001, also confirms a significant positive relationship between economic deepening and economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As regards the studies that find evidence for the positive effect of financialization on economic growth; Le et al (2019) employ the difference GMM technique in analysing the effect of financial depth on economic growth within the ASEAN+3 countries over the period 2000-2014. They find that stock market capitalisation has a positive impact on economic growth.…”
Section: Empirical Reviewmentioning
confidence: 99%